Resource allocation and growth strategies in a multi‐plant firm: Kanegafuchi Spinners in the early 20th century - Yamaguchi, Shotaro; Braguinsky, Serguey; Okazaki, Tetsuji; Yuki, Takenobu (Strategic Management Journal, 2023)
Abstract Research Summary Using detailed plant‐ and individual‐level data from a major Japanese cotton spinning company in the early 20th century, we examine the within‐firm allocation of skilled human capital in conjunction with investment in physical capital, accompanying the firm's evolving strategic priorities. We show that the firm leveraged unit‐level two‐way complementarity between managerial talent and strategically important plants when the task was achieving large‐scale output and positioning for a competitive cost advantage. The task of conducting product differentiation, however, ushered in “three‐way complementarity,” where educated engineering human capital and capable managers needed to be bundled with specialized physical capital. A deeper dive into the “nano‐economics” of resource allocation reveals that educated engineers experiencing product differentiation in pioneering plants were reallocated to other plants also pursuing product differentiation. Managerial Summary Effectively allocating critical resources, such as skilled human capital, across establishments in alignment with strategic priorities is a key managerial issue. Through an in‐depth case study of a major Japanese cotton spinning company in the early 20th century, we illustrate how the company shifted the resource allocation policy in response to different strategic management priorities. Initially, the company assigned managerial talent to larger plants requiring operational improvement, leveraging a competitive cost advantage for a standard product. Yet, as the company transitioned toward product differentiation via new production technologies, skilled engineers and plant managers were allocated together to a few selected plants initiating product differentiation. Engineers' experiences in product differentiation in those selected plants were diffused to other plants also pursuing product differentiation through their reallocations.